2013
DOI: 10.1161/circimaging.113.000482
|View full text |Cite
|
Sign up to set email alerts
|

T 1 Mapping With Cardiovascular MRI Is Highly Sensitive for Fabry Disease Independent of Hypertrophy and Sex

Abstract: Background-Fabry disease (FD) is an X-linked disorder of lysosomal metabolism affecting multiple organs with cardiac disease being the leading cause of death. Current imaging evaluations of the heart are suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(151 citation statements)
references
References 56 publications
(78 reference statements)
11
124
1
4
Order By: Relevance
“…T1 values in patients with AFD also correlated inversely with left ventricular wall thickness, whereas T1 values of the infero-lateral wall were elevated when LGE was present [7]. Furthermore, Thompson et al showed that reduced non-contrast myocardial T1 values are the most sensitive and specific cardiovascular MRI parameter in patients with AFD irrespective of sex and LV morphology and function [71]. ECV in AFD is normal compared to healthy volunteers whereas ECV is higher in other diseases [72].…”
Section: Anderson Fabry Disease (Afd)mentioning
confidence: 99%
“…T1 values in patients with AFD also correlated inversely with left ventricular wall thickness, whereas T1 values of the infero-lateral wall were elevated when LGE was present [7]. Furthermore, Thompson et al showed that reduced non-contrast myocardial T1 values are the most sensitive and specific cardiovascular MRI parameter in patients with AFD irrespective of sex and LV morphology and function [71]. ECV in AFD is normal compared to healthy volunteers whereas ECV is higher in other diseases [72].…”
Section: Anderson Fabry Disease (Afd)mentioning
confidence: 99%
“…In FD, low native T1 values specify myocardial involvement from glycosphingolipid accumulation. 10,11 The international multicenter nature of this study underscores its generalizability and distinguishes the scientific rigor of this study.…”
Section: Constancy Of Spatial Variation In Diffuse Myocardial Diseasementioning
confidence: 94%
“…30 From a treatment perspective, CMR can play an important role in identifying patients with fibrosis as well as those without hypertrophy but with increased extracellular volume. 31 There are recent reports showing ERT has no apparent effect on the rate of sudden cardiac death in patients with advanced disease. 32 Notwithstanding, ERT should be considered in patients with cardiac disease and started as early as possible when the benefit may be the most.…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%